METHODOLOGY FOR DEVELOPING STUDENTS' PHYSICAL AND TECHNICAL ABILITIES THROUGH PROBLEMS OF TECHNICAL CONTENT - Astanova Dilsuz Omonova (Bright Mind Publishing, 2025)
This article provides a theoretical and methodological analysis of the methodology for developing students' physical and technical abilities through solving problems of technical content in the mechanics section of the 7th-grade physics course. The introductory part substantiates the relevance of the topic and highlights the role of problems of technical content in the formation of scientific and technical thinking and practical skills in students. The methods section presents the stages of selecting, setting, and solving problems, as well as a table of sample problems. The results section describes the knowledge, skills, thinking, and personal qualities that students develop as a result of using this methodology. The discussion section presents the advantages, difficulties, and practical recommendations of the methodology. In conclusion, it is emphasized that solving problems of technical content serves not only to deepen the understanding of physics but also to form an interest in technology and engineering among students.
Keywords: Physics education, problems of technical content, mechanics, physical and technical abilities, methodology, 7th grade, technical thinking, problem solving, scientific and methodological approach, practical skills.